2016
DOI: 10.1097/anc.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Reduction in Bloodstream Infections in Infants at a Large Tertiary Care Neonatal Intensive Care Unit

Abstract: Purpose Reduction of bloodstream infections (BSI) has emerged as an important patient safety goal. Implementation of central line insertion bundles, standardized line care protocols, and health care provider education programs have reduced BSI in neonatal intensive care units (NICUs) around the country. The ability of large tertiary care centers to decrease nosocomial infections, including BSI, has been demonstrated. However, long-term BSI reductions in infants are not well documented. We sought to demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…The number of extremely premature infants with a positive blood culture (37% of all extremely premature infants in the units, EOS and LOS), is in line with international reports (45,46). It confirms the need for new strategies to prevent infections in these vulnerable neonates.…”
Section: Discussionsupporting
confidence: 80%
“…The number of extremely premature infants with a positive blood culture (37% of all extremely premature infants in the units, EOS and LOS), is in line with international reports (45,46). It confirms the need for new strategies to prevent infections in these vulnerable neonates.…”
Section: Discussionsupporting
confidence: 80%
“…In 2001, we introduced an educational campaign to prevent lung injury and established written guidelines to promote a consistent approach to caring for extremely premature infants. In 2007, we initiated an infection control program that resulted in a significant reduction in bloodstream infections [25]. In 2008, we began using donor breast milk in place of preterm formula when mother’s milk was unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…It was identified a lack of studies about this theme related to this specific population, being this, one of the limiting factors of the study. (9,(24)(25)(26)(27) Adherence to the use of bundle has shown significant results in reducing CLABSI in NICU, linked to permanent education practices. (9,26) A meta-analysis aimed at evaluating the efficacy of bundles of CLABSI prevention in neonatal, pediatric and adult Intensive Care Unit, identified that this strategy implementation in different countries presents positive results in costs reduction.…”
Section: Discussionmentioning
confidence: 99%
“…(9,24) Regarding the exchange of the stopcocks and connectors, item 4 of the Bundle, it was followed the guidelines of The Brazilian Health Regulatory Agency (ANVISA -Agência Nacional de Vigilância Sanitária), with the recommendation to perform it immediately when there are clots present or after collection of blood or administration of blood products, and with interval less than 96 hours if they remain unchanged; confirming the recommendations of other studies. (16,25,27) Item 5 includes the performance of the permeability test of the access before and after the use, to minimize the return of blood to the lumen of the Perform hand hygiene for 40 to 60 seconds, before and after handling the PICC with antiseptic solution of chlorhexidine gluconate and/or 70% alcohol gel; use procedure gloves and take off adornments.…”
Section: Discussionmentioning
confidence: 99%